2018
DOI: 10.1111/1755-0998.12895
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing polymerase biases in metabarcoding

Abstract: DNA metabarcoding is an increasingly popular method to characterize and quantify biodiversity in environmental samples. Metabarcoding approaches simultaneously amplify a short, variable genomic region, or "barcode," from a broad taxonomic group via the polymerase chain reaction (PCR), using universal primers that anneal to flanking conserved regions. Results of these experiments are reported as occurrence data, which provide a list of taxa amplified from the sample, or relative abundance data, which measure th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
175
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 186 publications
(188 citation statements)
references
References 83 publications
(116 reference statements)
3
175
0
Order By: Relevance
“…Sources of bias, particularly isolation and amplification biases have been examined in detail for microbiological studies (Brooks et al., ), but not for studies on pollen, and very few for any other complex eukaryotes (Nichols et al. ). While most of these biases will be the same regardless of the sample type, for DNA isolation efficiency and marker copy number, the properties of pollen will differ from other organisms, or even other tissue types within plants.…”
Section: Discussionmentioning
confidence: 99%
“…Sources of bias, particularly isolation and amplification biases have been examined in detail for microbiological studies (Brooks et al., ), but not for studies on pollen, and very few for any other complex eukaryotes (Nichols et al. ). While most of these biases will be the same regardless of the sample type, for DNA isolation efficiency and marker copy number, the properties of pollen will differ from other organisms, or even other tissue types within plants.…”
Section: Discussionmentioning
confidence: 99%
“…BIN accumulation curves indicated that the read depth employed in this study allowed all four treatments to meet a slope of < 0.01. However, the Single Leg treatment reached this value with much lower read depth than the bulk samples due to its relative protection from the impacts of PCR bias (Nichols et al ; Pan et al, , Dabney & Meyer, ; Elbrecht & Leese, ). Interestingly, the other three treatments showed similar BIN accumulation curves on all three sequencers, suggesting shared factors constrain BIN recovery.…”
Section: Discussionmentioning
confidence: 99%
“…The Miseq produced the highest quality reads, suggesting that the higher incidence of unmatched reads on the Ion Torrent platforms reflect, in part, sequencing errors, especially the PGM which has a steep decline in quality towards the 3’ end (Supporting Information Figure S1). PCR errors introduced by the DNA polymerase can be exacerbated by sequencing errors (Dabney & Meyer, ; Nichols et al, ; Pan et al, ). Because long amplicons improve taxonomic resolution, their use should be standard for metabarcoding studies unless template DNA is degraded.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations